2017
DOI: 10.1111/iwj.12719
|View full text |Cite
|
Sign up to set email alerts
|

Novel foam dressing using negative pressure wound therapy with instillation to remove thick exudate

Abstract: We describe our experience with a novel foam dressing architecture in tandem with negative pressure wound therapy and instillation (NPWTi-d) for removing viscous wound exudate and infectious materials. A retrospective review was conducted of the outcomes of 21 patients who received NPWTi-d using a reticulated open cell foam instillation dressing with through holes (ROCF-CC) designed to facilitate the removal of thick wound exudate and infectious materials. NPWTi-d with ROCF-CC was used to treat large complex c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 14 publications
0
38
0
2
Order By: Relevance
“…In the first published peer-reviewed paper by Téot et al, they showed reduction in the surface area of black non-viable tissue and yellow fibrinous slough to less than 10% in 18 out of 21 patients (85.7%) and 15 out of 21 (71.4%) wounds had ≤20% surface area with yellow fibrinous slough remaining. Of 21 wounds, 20 (95.2%) displayed enhanced granulation tissue formation and reduction in wound volume [9]. In all of our three cases, all the wounds had less than 5% remaining surface area with yellow slough.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…In the first published peer-reviewed paper by Téot et al, they showed reduction in the surface area of black non-viable tissue and yellow fibrinous slough to less than 10% in 18 out of 21 patients (85.7%) and 15 out of 21 (71.4%) wounds had ≤20% surface area with yellow fibrinous slough remaining. Of 21 wounds, 20 (95.2%) displayed enhanced granulation tissue formation and reduction in wound volume [9]. In all of our three cases, all the wounds had less than 5% remaining surface area with yellow slough.…”
Section: Discussionmentioning
confidence: 88%
“…VERAFLO CLEANSE CHOICE™ Dressing is a novel, adjunctive non-surgical option that may help clean large complex wounds when complete surgical debridement is not possible or appropriate. Prior to our paper, only eight articles using this type of dressing have been published, all are case reports of one or two cases except one [9-11]. In the first published peer-reviewed paper by Téot et al, they showed reduction in the surface area of black non-viable tissue and yellow fibrinous slough to less than 10% in 18 out of 21 patients (85.7%) and 15 out of 21 (71.4%) wounds had ≤20% surface area with yellow fibrinous slough remaining.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Teot et al [25] described their experience with NPWTi-d ROCF-CC in patients with large complex chronic wounds, including PrUs, that contained viscous wound exudate and areas of devitalized tissue. They reported that the ROCF-CC dressing "assisted in loosening, solubilizing, and detaching viscous exudate, dry fibrin, wet slough, and other infectious materials [25]. "…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, several published reviews and recommendations exist for the use of NPWTi-d in acute and chronic wounds [15,16,24]. Specific dressings for use with NPWTi-d have also been developed, including a reticulated open cell foam dressing with through holes (ROCF-CC) that assists in removing thick wound exudate and infectious materials [25]. ROCF-CC may be especially helpful for wound cleansing when surgical debridement must be delayed or is not possible or appropriate.…”
Section: Introductionmentioning
confidence: 99%